Preliminary study on the safety and efficacy of a newly manufactured STVac7 vaccine against pneumonic mannheimiosis of goats - Salleh, Annas; Pakiman, Norazrina; Sharidon, Syafiqah Adilah; Rohzaili, Nuralia Raihana; Zamri-Saad, Mohd (Universiti Putra Malaysia, 2026)
Pneumonic mannheimiosis is a respiratory disease of small ruminants caused by Mannheimia haemolytica. It leads to deaths and great economic loss, and the most effective control measure is through vaccination. This study evaluates the safety and efficacy of a newly manufactured STVac7 vaccine in goats against M. haemolytica. Five groups of goats with 3 goats per group received either freshly prepared vaccines (Group 1), 21-month-old formulations (Group 2), high dose vaccination (Group 3), vaccine containing a stabiliser and preservative (Group 4) and control, no vaccination (Group 5). Key clinical signs, including respiratory rates, body temperatures and adverse events, particularly sneezing and coughing, were monitored throughout the 12-week study period. All goats were challenged with 109 CFU/mL of live M. haemolytica in week 10. Following vaccination, mild sneezing and coughing were occasionally observed. Post-challenge, clinical signs were most severe in the control Group 5, while M. haemolytica was isolated from all groups, with a higher frequency in the control Group 5. This was consistent with the more severe gross and histopathological lung lesions in control Group 5, while bronchus-associated lymphoid tissue (BALT) was mostly observed in Group 1 and least observed in control Group 5. Subsequently, high levels of IgG were detected in vaccinated goats, particularly Group 4. Fibrinous bronchopneumonia, a key lesion of pneumonic mannheimiosis was observed only in the control Group 5. In summary, the STVac7 vaccine is safe and effective in protecting goats from severe pneumonic mannheimiosis.